2021
DOI: 10.3389/fmicb.2021.692069
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the IFN Response by Bluetongue Virus: The Story So Far

Abstract: Bluetongue virus (BTV) is the prototypical orbivirus that belongs to the Reoviridae family. BTV infection produces a disease in ruminants, particularly in sheep, that results in economic losses through reduced productivity. BTV is transmitted by the bite of Culicoides spp. midges and is nowadays distributed globally throughout subtropical and even temperate regions. As most viruses, BTV is susceptible to the IFN response, the first line of defense employed by the immune system to combat viral infections. In tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 124 publications
(242 reference statements)
0
8
0
Order By: Relevance
“…NS1 promotes viral protein expression [ 25 ]; NS2 is an RNA binding protein which is the main component of viral inclusion bodies [ 26 ]; while NS3 is involved in virion egress [ 27 , 28 , 29 ]. VP3, NS3, NS4, and the putative NS5 are involved in impairing the host cellular response to BTV by acting as interferon antagonist and/or by promoting cellular shut-off [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Bluetongue Virus: the Prototypical Orbivirusmentioning
confidence: 99%
See 1 more Smart Citation
“…NS1 promotes viral protein expression [ 25 ]; NS2 is an RNA binding protein which is the main component of viral inclusion bodies [ 26 ]; while NS3 is involved in virion egress [ 27 , 28 , 29 ]. VP3, NS3, NS4, and the putative NS5 are involved in impairing the host cellular response to BTV by acting as interferon antagonist and/or by promoting cellular shut-off [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Bluetongue Virus: the Prototypical Orbivirusmentioning
confidence: 99%
“…Once BTV reaches the LN, it can disrupt follicular DC activity [ 94 ]. BTV has the capacity to replicate in ruminants in presence of a concomitant antiviral IFN response (reviewed in [ 34 ]). We have shown that BTV presence in the LN triggered the expression of the IFN-stimulated gene Mx1 [ 94 ].…”
Section: Btv Disruption Of Adaptive Immunitymentioning
confidence: 99%
“…43 The reason for the stunted response is unclear. In sheep, BTV has been reported to antagonize interferon synthesis and might be able to downregulate the innate immune response, 46 possibly interfering with the synthesis of SAA. African horse sickness virus nonstructural protein 4 has recently been demonstrated to contribute to potential mechanisms to overcome the host's antiviral response by colocalization with promyelocytic leukemia nuclear bodies 47 and interference with the JAK-STAT pathway that is instrumental in the interferon pathway.…”
Section: Discussionmentioning
confidence: 99%
“…VP3, NS3, NS4 and the putative NS5 are involved in countering the antiviral cell response. VP3, NS3 and NS4 can act as IFN antagonists (reviewed in [34]). VP3 can impair IFN induction [35], while NS3 and NS4 can counter IFN induction as well as type I and type II IFN signaling [36][37][38][39][40].…”
Section: Figure 1 Schematic Representation Of Bluetongue Virus (Btv) (A)mentioning
confidence: 99%